Nonylphenol exacerbates ovalbumin-induced allergic rhinitis via the TSLP-TSLPR/IL-7R pathway and JAK1/2-STAT3 signaling in a mouse model - Yunxiu Wang; Zhiwei Cao; He Zhao; Zhaowei Gu (Ecotoxicology and Environmental Safety, 2022)
Nonylphenol (NP) can be widely used as a plasticizer, surfactant, antioxidant, textile printing, dyeing additive, and pesticide emulsifier. Animal studies have shown that NP aggravates ovalbumin (OVA)-induced allergic rhinitis (AR); however, the exact mechanism underlying its action has not yet been detailed. This study aimed to explore the aggravation of the AR inflammatory response following NP exposure and its possible mechanism. The AR mouse model was constructed using OVA. Under NP exposure, allergic nasal symptoms were observed, eosinophil infiltration was assessed by Sirius red staining, and the levels of IL-4, IL-5, and IL-13 in nasal mucosa samples were detected using cytometric bead array. The mRNA levels of OX40/OX40L and GATA3 in nasal mucosa were detected by qPCR, and the expression levels of the TSLP and JAK1/2-STAT3 signaling pathway components were also identified. Our results suggest that NP exposure exacerbated allergic nasal symptoms and that eosinophils accumulated in nasal mucosa after OVA challenge. The levels of the typical T helper 2 cytokines, as well as the mRNA levels of OX40/OX40L and GATA3, were elevated in the nasal mucosa of OVA-challenged mice exposed to NP. In addition, NP exposure elevated the TSLP, TSLPR, IL-7R, p-JAK1, p-JAK2, and p-STAT3 levels in the nasal mucosa after OVA stimulation. Overall, the present study suggests NP can exacerbate OVA-induced AR inflammatory responses; furthermore, this aggravating effect of NP may be related to the TSLP-TSLPR/IL-7R and JAK1/2-STAT3 signaling pathways.